Wheaton, Pottawatomie County - Barnes, Cameron (Kansas State University, The Chapman Center for Rural Studies, 2011)
Founded in 1881 by individuals of German Heritage, Wheaton grew to a town with three newspapers and made early technology advancements of telephone poles and gas generator. Although the town has dwindled and the school consolidated with Onaga, the Kufahl Family hardware store is still in operation after a century.
Cameron Barnes, “Wheaton, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/53.
Keywords: Kufahl; Onaga; Pottawatomie County; School; Wheaton; Cameron Barnes